If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11.5(4 + X) = 0 (4 * 11.5 + X * 11.5) = 0 (46 + 11.5X) = 0 Solving 46 + 11.5X = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-46' to each side of the equation. 46 + -46 + 11.5X = 0 + -46 Combine like terms: 46 + -46 = 0 0 + 11.5X = 0 + -46 11.5X = 0 + -46 Combine like terms: 0 + -46 = -46 11.5X = -46 Divide each side by '11.5'. X = -4 Simplifying X = -4
| 5z+5=6-4z+17 | | 6=a+9 | | sec*x-secx-2=0 | | 2(2y+1)=(5y-2) | | 5x+9+4x=9+8+(-7) | | log(9x^3)=2 | | 7a^2-5a-5=-5 | | X^2-25=10 | | 2(25-5)=2(26+5) | | 5x+9+4x=9+8 | | 21/3×5-11 | | 2/7=x/7 | | (X^-3y^3)^-4/(y^3x^-5)^-5 | | 8x^(13/3)-24=0 | | 2*cosx=2*cos*2x | | 12z-4x=-7 | | 10h-10=10-10h | | x^9/2 | | 38x+66=180 | | 3x-(5x)= | | 2n-4=5n+5 | | 80x^2-720=0 | | 8=3x+bx | | 12z+4x=-7 | | 27q-9=180 | | 112x^2-56x=0 | | 2y-7=5-y | | x+.7y=238 | | z=2+3i | | 6n+3+15n+48+3n+10= | | 16r^2-121=0 | | 2/7x7/1 |